铁细菌在北极特定海区沉积物中的分布 - 高爱国; 陈皓文 (2008)
用平板法对取自北极加拿大海盆和楚科奇海10个沉积物岩芯中184个样品进行铁细菌检出率和含量分析。结果表明,4℃培养时铁细菌的检出率为10.33%,含量范围均为未检出~8.40×106个/g(湿样,下同),平均含量为7.76×104个/g。25℃培养时铁细菌的检出率为40.22%,含量范围均为未检出~1.00×108个/g,平均含量为1.40×106个/g。研究区沉积物中铁细菌含量高于太平洋深海沉积物中铁细菌含量;与前人在淡水沉积物中所作的调查相比,研究区的铁细菌含量落在前人调查结果范围内,但比细菌簇中铁细菌含量要低,这表明研究区海底沉积物的微生境较适合铁细菌的繁衍。对铁细菌在不同水深、经纬度以及沉积物深度中的分布进行了讨论,结果表明铁细菌检出率随沉积物深度增加而增大,含量变化呈现出浅层少、下层多之势。铁细菌的纬度分布范围较大,并显出有扩大的趋势。铁细菌含量与检出率随水深加大也呈跳跃式变化,水较深时铁细菌有较高的检出率和数量,但离陆距离的增加又会在物质供应上对其生长产生制约。培养温度对铁细菌分布有一定影响,温度提高不仅提高了铁细菌检出率,也增加了铁细菌的含量。这也许与部分铁细菌的最适宜生长温度较高有关,温度升高有利于某些铁细菌的生长发育。 Analyses of iron-oxidizing bacteria(FeOB) were made of 184 samples of 10 sediment cores from the Canada Basin and the Chukchi Sea by means of plate culture,and their occurrence percentages and contents were studied.The results have shown that the occurrence percentages of FeOB in the samples cultivated at 4 ℃ and 25 ℃ are 10.33% and 40.22% respectively and the contents of FeOB(in wet samples,the same hereinafter) range from non-detected(ND) to 8.40×106 CFU/g,with an average of 7.76×104 CFU/g,in the samples cultivated at 4 ℃ and from ND to 1.00×108 CFU/g,with an average of 1.40×106CFU/g,in the samples cultivated at 25 ℃.The contents of FeOB in the sediment cores of the study area are higher than those in the abyssal sediments of the Pacific Ocean.Compared with previous studies carried out in fresh water,the FeOB contents in the study area are all dropped in the range of the previous results,but are lower than those in the bacteria mat.This indicates that the micro-habitat-environment in the sediments of the study area is favorable for the regeneration of FeOB. The distributions of FeOB in different water depth,different longitude and latitude and different sedimentary depth have been discussed.It has been shown that the occurrence percentages of FeOB tend to increase with sedimentary depth and the contents of FeOB tend to be lower in the shallow layers and higher in the deeper layers.The latitudinal distributions of FeOB show a wide range and an expanding tendency.The occurrence percentages and contents of FeOB increase with water depth and vary in a jumping way.Higher occurrence percentages and contents of FeOB occur in relatively deeper water.With increasing in distance away from the coast,however,the growth of FeOB has been restricted due to the lack of nutrient matter supply.The cultivation temperature can also exert influences,to certain extent,to the distributions of FeOB.With the increasing in temperature not only the occurrence percentage but also the content of FeOB is increased.This may probably indicate that relatively higher temperature is more favorable for the growth of some of the FeOB. 国家自然科学基金项目——楚科奇海及其邻近海域沉积物中细菌生物地球化学(40576060);; 国家自然科学基金项目——楚科奇海沉积物中古环境变化的地球化学响应(40376017)